Pengaruh Akuntabilitas Dan Transparansi Pemerintah Desa Terhadap Pengelolaan Alokasi Dana Desa Pada Desa Detubinga Kecamatan Tanawawo - Balsano Amryanto Bhoka; Andreas Rengga; Wihelmina Maryetha Yulia Jaeng (BADAN PENERBIT STIEPARI PRESS, 2023)
Government accounting has a role in managing public finances in order to realize good governance, starting from central, regional and village financial governance. Principles in government accounting such as transparency and accountability in managing public finances are not only a form of obligation from the central government, but also regions such as villages. The village as a government organizational unit that deals directly with the community with all backgrounds, interests and needs has a very important role.